The Evolving Paleobathymetry of the Circum-Antarctic Southern Ocean Since 34 Ma: A Key to Understanding Past Cryosphere-Ocean Developments - Hochmuth, K.; Gohl, K.; Leitchenkov, G.; Sauermilch, I.; Whittaker, J. M.; Uenzelmann-Neben, G.; Davy, B.; De Santis, L. (FID GEO, 2020)
The Southern Ocean is a key player in the climate, ocean, and atmospheric system. As the only direct connection between all three major oceans since the opening of the Southern Ocean gateways, the development of the Southern Ocean and its relationship with the Antarctic cryosphere has influenced the climate of the entire planet. Although the depths of the ocean floor have been recognized as an important factor in climate and paleoclimate models, appropriate paleobathymetric models including a detailed analysis of the sediment cover are not available. Here we utilize more than 40 years of seismic reflection data acquisition along the margins of Antarctica and its conjugate margins, along with multiple drilling campaigns by the International Ocean Discovery Program (IODP) and its predecessor programs. We combine and update the seismic stratigraphy across the regions of the Southern Ocean and calculate ocean-wide paleobathymetry grids via a backstripping method. We present a suite of high-resolution paleobathymetric grids from the Eocene-Oligocene Boundary to modern times. The grids reveal the development of the Southern Ocean from isolated basins to an interconnected ocean affected by the onset and vigor of an Antarctic Circumpolar Current, as well as the glacial sedimentation and erosion of the Antarctic continent. The ocean-wide comparison through time exposes patterns of ice sheet development such as switching of glacial outlets and the change from wet-based to dry-based ice sheets. Ocean currents and bottom-water production interact with the sedimentation along the continental shelf and slope and profit from the opening of the ocean gateways.